The experience of informal caregivers in providing patient care in hospitals in low- and middle-income countries: A qualitative meta-synthesis. Issue 4 (October 2022) - Hogan, Unarose; Bingley, Amanda; Morbey, Hazel; Walshe, Catherine
Objective: In low- and middle-income countries, informal caregivers frequently stay in hospitals and perform patient care tasks typically performed by nurses in other contexts. This article reviews qualitative research on these informal caregivers, to gain insight and understanding of their experiences. Methods: We undertook a qualitative meta-synthesis. Relevant literature was identified through searches of electronic databases in 2021. Thematic analysis was conducted to facilitate the identification of conceptual relationships to formulate synthesised findings. Results: Twenty-four studies met the inclusion criteria – 13 from Sub-Saharan Africa, five from Bangladesh, two from India, two from Iran, one from Brazil and one from Peru. Three themes were generated from the meta-synthesis: (1) The unwelcome but tolerated guest, (2) Enduring personal sacrifice and (3) Fulfilling familial obligations. These themes emphasised the significant burden associated with the hospital caregiving experience and highlighted the implicit reliance on informal caregivers in low- and middle-income countries. Conclusions: Informal caregivers perform an essential caregiving role, yet occupy a peripheral and voluntary space in hospitals. There is a clear need to support informal caregivers so that they can safely perform their tasks.